High mobility group box 1 protein in bronchoalveolar lavage fluid, correlations with other markers of inflammation and differences in lung diseases - Suchankova, Magda; Durmanova, Vladimira; Tibenska, Elena; Tedlova, Eva; Majer, Ivan; Novosadova, Helena; Demian, Juraj; Tedla, Miroslav; Bucova, Maria (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Objectives: Analysis of new markers in bronchoalveolar lavage fluid (BALF) provides new insights into the immunopathogenesis and may be helpful in differential diagnosis of lung diseases. High mobility group box 1 protein (HMGB1) is a non-histone nuclear protein and its release into the extracellular environment may be associated with the inﬂammatory response. The aim of the study is the analysis of HMGB1 in BALF, correlations with other markers of inflammation and differences in extracellular HMGB1 levels in various lung diagnoses. Methods: The concentration of HMGB1 was tested by an Elisa test. We calculated correlations with other inflammatory markers (leukocytes, total protein, albumin, IgG, IgA, IgM, C3 complement component, alpha-2macroglobuline, CD3, CD4, CD8, TREM-1 and TREM-2) and specified HMGB1 level in various diagnoses. Results: A positive correlation was found between the level of HMGB1 and total protein levels (p=0.0001), albumin (p=0.0058), IgA (p=0.011), IgM (0.0439) and TREM-2 (p=0.0188). Conversely, a negative correlation was revealed between HMGB1 and TREM-1 (p=0.0009). HMGB1 level varied in different diagnoses: the highest level was detected in QuantiFERON TB-positive subjects (median: 30.2) and hypersensitivity pneumonitis (median: 33.2), followed by pulmonary sarcoidosis (median: 16.8) and idiopathic pulmonary fibrosis (median: 8.8). Conclusion: HMGB1 correlates with other inflammatory markers tested in BALF. Its level varies in different lung diagnoses.